2021
DOI: 10.15388/crimlithuan.2021.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Social Research about Online Crime: Global Range of Topics and a Systematic Analysis of Research in Lithuania

Abstract: Social research about online crime is a multi-disciplinary field addressing a wide array of topics since its inception in the 1980s. Based on a broad review of state-of-the-art literature and gaps identified in review publications (Holt, Bossler 2014; Stratton, Powell, Cameron 2017; Maimon, Louderback 2019, and others), in this paper I outline 41 key topic in social research about online crime, classified into four broad categories: 1) research focusing on specific types of online crime, 2) research about perp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…In part, Nigerian youths have been disproportionately implicated in internet crimes ( Adogame, 2009 ; Ibrahim, 2016 ; Hall et al., 2020 ). Likewise, in a digital age, local criminals' actions have international connections and consequences, as many authors have suggested ( Hall et al., 2020 ; Hall and Hudson, 2022 ; Jaishankar, 2018 ; Leukfeldt et al., 2020 ; Lewis, 2020 ; Ndubueze, 2020 ; Šupa, 2021 ; Rich, 2017 ; Wall, 2013 ; Zakari and Button, 2021 ). Similarly, a study interviewed 40 EFCC officers ( Lazarus and Okolorie, 2019 ), and another interviewed 40 cybercriminals ( Aransiola and Asindemade, 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In part, Nigerian youths have been disproportionately implicated in internet crimes ( Adogame, 2009 ; Ibrahim, 2016 ; Hall et al., 2020 ). Likewise, in a digital age, local criminals' actions have international connections and consequences, as many authors have suggested ( Hall et al., 2020 ; Hall and Hudson, 2022 ; Jaishankar, 2018 ; Leukfeldt et al., 2020 ; Lewis, 2020 ; Ndubueze, 2020 ; Šupa, 2021 ; Rich, 2017 ; Wall, 2013 ; Zakari and Button, 2021 ). Similarly, a study interviewed 40 EFCC officers ( Lazarus and Okolorie, 2019 ), and another interviewed 40 cybercriminals ( Aransiola and Asindemade, 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crime script analysis provides a framework for understanding the procedures of a criminal act from the point of view of the criminal (Lee, 2020), outlining the steps and actions that perpetrators go through to prepare for, undertake and complete the scam. The scripts fit the concept of schemas in cognitive science and are seen to be a special type of "event" schema that organises our knowledge about how to understand and enact everyday behavioural processes or routines in certain situations (Hutchings & Holt, 2014).…”
Section: Crime Scriptsmentioning
confidence: 99%